Targeting of the intracellular redox balance by metal complexes towards anticancer therapy - Murillo, María Isabel; Gaiddon, Christian; Le Lagadec, Ronan (Frontiers in Chemistry, 2022)
The development of cancers is often linked to the alteration of essential redox processes, and therefore, oxidoreductases involved in such mechanisms can be considered as attractive molecular targets for the development of new therapeutic strategies. On the other hand, for more than two decades, transition metals derivatives have been leading the research on drugs as alternatives to platinum-based treatments. The success of such compounds is particularly due to their attractive redox kinetics properties, favorable oxidation states, as well as routes of action different to interactions with DNA, in which redox interactions are crucial. For instance, the activity of oxidoreductases such as PHD2 (prolyl hydroxylase domain-containing protein) which can regulate angiogenesis in tumors, LDH (lactate dehydrogenase) related to glycolysis, and enzymes, such as catalases, SOD (superoxide dismutase), TRX (thioredoxin) or GSH (glutathione) involved in controlling oxidative stress, can be altered by metal effectors. In this review, we wish to discuss recent results on how transition metal complexes have been rationally designed to impact on redox processes, in search for effective and more specific cancer treatments